PENDIDIKAN ISLAM DI SPANYOL - Mulyadi Hermanto Nasution (Universitas Muhammadiyah Tapanuli Selatan, 2017)
This paper provides a brief overview of the development of Islamic education. One thing that is interesting that the transition of civilization of the Islamic world to the European part can occur through the development of Islamic education in stages, making European civilization can rise up to this day. The progress of the European world to date has a very dynamic history. This is seen by the many scholars who can trace the progress through the process of in-depth review. Therefore, it can be stated that the existence of Islamic educational process in Spain can provide influenced by the opening of the realm of philosophy as one of the main keys in the birth of various disciplines in Islam.